BIO-ENVIRONMENTAL REDESIGN AND ENERGY EFFICIENCY OF RURAL SCHOOL IN VILLA SILIPICA-SANTIAGO DEL ESTERO - Giuliano Raimondi, Gabriela (Facultad de Arquitectura, Urbanismo y Diseño, 2020)
The present work exposes a design with bioenvironmental adaptation of a state school prototype, as an overcoming alternative for the province of Santiago del Estero, with a warm semi-arid climate. It was diagnosed in the summer period through a hygrothermal audit, with subjective evaluation, a socio-environmental and objective survey, thermal simulation and on-site monitoring, together with verification of the series of IRAM standards on hygrothermal habitability conditions and energy efficiency. Based on the calculation values obtained, it was determined that they do not comply with those recommended for hygrothermal comfort; This was affirmed by the students, who stated that they felt uncomfortable on a day with weather conditions representative of the study period; in addition, in the measured and modeled building thermal behavior, both showed deficiencies. Therefore, a redesign project with incorporation of bioenvironmental guidelines was proposed, analyzing results comparatively with respect to the state prototype. It was concluded that with adjustments made on aspects: dimensional, orientation, incorporation of inertia and thermal insulation in opaque casing and hermeticity in non-opaque casing, with carpentry of better energy performance, among other decisions; it is possible to optimize the thermal-energetic performance to parameters of efficiency and interior comfort in classrooms.